StrayCats. II. An Updated Catalog of NuSTAR Stray Light Observations - Ludlam, R. M.; Grefenstette, B. W.; Brumback, M. C.; Tomsick, J. A.; Buisson, D. J. K.; Coughenour, B. M.; Mastroserio, G; Wik, D.; Krivonos, R.; Jaodand, A. D.; Madsen, K. K. (The Astrophysical journal, 2022)
We present an updated catalog of StrayCats (a catalog of NuSTAR stray light observations of X-ray sources) that includes nearly 18 additional months of observations. StrayCats v2 has an added 53 sequence IDs, 106 rows, and three new identified stray light (SL) sources in comparison to the original catalog. The total catalog now has 489 unique sequence IDs, 862 entries, and 83 confirmed StrayCats sources. Additionally, we provide new resources for the community to gauge the utility and spectral state of the source in a given observation. We have created long-term light curves for each identified SL source using MAXI and Swift/BAT data when available. Further, source extraction regions for 632 identified SL observations were created and are available to the public. In this paper we present an overview of the updated catalog and new resources for each identified StrayCats SL source.